Financing Climate Resilience from the Bottom Up : A Perspective on Reimagining Pradhan Mantri Mudra Yojana as India’s Micro-Green Bank - Shetty, Nishmitha; Ramaprasad, Badrinarayan Srirangam; Praveen, Shilpa (Indian Journal of Finance, 2026)
Purpose : This perspective explored the untapped potential of the Pradhan Mantri Mudra Yojana (PMMY) as a channel for climate finance, with particular emphasis on its extensive reach among women borrowers and micro-enterprises in India. It argued for the introduction of a “Green-Mudra” initiative that leveraged existing financial architectures to promote climate-positive economic activities at scale. Design/Methodology/Approach : The perspective proposed the addition of a simple “green tag” to Mudra loan applications and the integration of climate-relevant variables into existing credit-scoring methods. It also suggested that the aggregated carbon benefits of numerous small loans could have been pooled to finance a modest interest rebate, without requiring legislative amendments or new subsidies. Findings : Illustrations drawn from five climate-positive examples—namely electric vehicle services, solar irrigation, village cold storage, biochar production, and electronics repair—demonstrated clear potential commercial viability, measurable environmental benefits, and substantial scope for inclusive entrepreneurship within the existing Mudra framework. Practical Implications : The proposed idea, grounded in a risk-aware economic rationale and supported by a monitoring system, could have mitigated repayment risks for lenders, directed climate capital more effectively to grassroots levels, and strengthened livelihood resilience among micro-entrepreneurs. Originality/Value : The article uniquely positioned PMMY as a readily adaptable instrument for climate finance and underscored the simplicity and efficiency of refining an existing successful program rather than creating new financial mechanisms. The “Green-Mudra” concept highlighted a pragmatic pathway toward rapid, scalable environmental and economic impacts.